Case Report and Review of the Literature: Congenital Diaphragmatic Hernia and Craniosynostosis, a Coincidence or Common Cause? - Gaillard, Linda; Goverde, Anne; van den Bosch, Quincy C. C.; Jehee, Fernanda S.; Brosens, Erwin; Veenma, Danielle; Magielsen, Frank; de Klein, Annelies; Mathijssen, Irene M. J.; van Dooren, Marieke F. (Frontiers in Pediatrics, 2021)
Congenital diaphragmatic hernia (CDH) is a life-threatening birth defect that presents as either an isolated diaphragm defect or as part of a complex disorder with a wide array of anomalies (complex CDH). Some patients with complex CDH display distinct craniofacial anomalies such as craniofrontonasal dysplasia or craniosynostosis, defined by the premature closure of cranial sutures. Using clinical whole exome sequencing (WES), we found a BCL11B missense variant in a patient with a left-sided congenital diaphragmatic hernia as well as sagittal suture craniosynostosis. We applied targeted sequencing of BCL11B in patients with craniosynostosis or with a combination of craniosynostosis and CDH. This resulted in three additional BCL11B missense mutations in patients with craniosynostosis. The phenotype of the patient with both CDH as well as craniosynostosis was similar to the phenotype of previously reported patients with BCL11B missense mutations. Although these findings imply that both craniosynostosis as well as CDH may be associated with BCL11B mutations, further studies are required to establish whether BCL11B variants are causative mutations for both conditions or if our finding was coincidental.